Implementasi Kompetensi Profesional Guru sebagai upaya Peningkatan Kualitas Pembelajaran - Herman, Maman; Tresna Hidayat, Gian; Kholisoh Nuryani, Lilis; Nugroho, Wahyu; Wahyuningsih, Dasini (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2023)
This research aims to investigate the quality of learning at Bingkeng 01 Public Elementary School over the past five years, which has not been optimal, particularly in relation to the implementation of teachers' professional competence. Teachers' professional competence is considered crucial for ensuring mastery of subject matter and the expected quality of learning. Employing a qualitative approach with a descriptive method, this study collected data through interviews, observations, documentation studies, and triangulation. The findings revealed that the implementation of teachers' professional competence has been generally adequate; however, there is room for improvement in teachers' skills and motivation. Challenges in optimizing teachers' professional competence encompass additional responsibilities beyond teaching duties, insufficient support from teachers' professional organizations, and inadequate educational facilities. Efforts to overcome these obstacles involve balancing teachers' additional tasks, motivating support from school principals, involvement in teacher work groups, and providing relevant educational facilities. In conclusion, enhancing the implementation of teachers' professional competence requires a comprehensive strategy involving school principals, professional teacher organizations, and the provision of suitable educational facilities.